Simulation and Stress Analysis of AISI 1045 Steel Bottom Plate in a Brake Handle Mold Assembly Using Finite Element Analysis - Nurjaya Nurjaya; Suwandi Nata Atmaja; Reson Wibowo; Jaja Miharja (Faculty of Engineering, Universitas Muhammadiyah Jakarta, 2026)
The accuracy and reliability of mold manufacturing are essential to ensure product quality and operational safety. Among mold components, the bottom plate of a brake handle mold plays a structurally critical role; however, previous studies have given limited attention to its mechanical performance. This research addresses that gap by performing a Finite Element Analysis (FEA) to evaluate the stress distribution, deformation, and safety factor of an AISI 1045 steel bottom plate. Static loading simulations of 60 N, 120 N, and 180 N representing typical operational forces in brake handle molds, were performed using SolidWorks 2020. The results revealed extremely low von Mises stresses (ranging from 3.96 × 10⁻² MPa to 1.195 × 10⁻³ MPa) and very small deformations (10⁻⁷ to 10⁻⁶ mm), producing unrealistically high safety factors (SF 44.6 to 133.7). These anomalies indicate inconsistencies between the numerical output and theoretical expectations, suggesting that the boundary conditions and load configurations used in the simulation may not fully represent actual working conditions. Despite these limitations, this study contributes to identifying how modeling assumptions influence FEA results and emphasizes the importance of model validation and refinement to achieve more realistic and reliable simulations for practical design optimization. Future work will focus on improving boundary condition definitions and conducting experimental validation to verify model accuracy.